2002
DOI: 10.1165/rcmb.2002-0033oc
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Arachidonate Release from Human Lung Cells through the Epithelial Growth Factor Receptor Pathway

Abstract: Oxidative stress is thought to be a factor influencing many inflammatory responses, including arachidonic acid (AA) release. We have studied the effect of hydrogen peroxide on AA and prostaglandin E(2) release, cytosolic phospholipase (cPLA(2)) steady-state mRNA, cPLA(2) protein levels, cPLA(2) enzyme activity, and cPLA(2) phosphorylation in a human lung epithelial cell line: A549 cells. Hydrogen peroxide caused a dose-dependent increase of A23187-stimulated AA and prostaglandin E(2) release, with a maximum ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
5
25
1
Order By: Relevance
“…Activation of PLA 2 contributed to upregulation of COX-2 in murine macrophages and human lung cells (Balsinde et al 1999;Pawliczak et al 2002Pawliczak et al ,2004. Furthermore, free AA activates a variety of proteins involved in the regulation of COX-2 expression, including p38 MAP kinase (Hii et al 1998), peroxisome proliferator-activated receptor γ (Pawliczak et al 2002(Pawliczak et al , 2004 and phosphatidyl inositol-3-kinase (Monick et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of PLA 2 contributed to upregulation of COX-2 in murine macrophages and human lung cells (Balsinde et al 1999;Pawliczak et al 2002Pawliczak et al ,2004. Furthermore, free AA activates a variety of proteins involved in the regulation of COX-2 expression, including p38 MAP kinase (Hii et al 1998), peroxisome proliferator-activated receptor γ (Pawliczak et al 2002(Pawliczak et al , 2004 and phosphatidyl inositol-3-kinase (Monick et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, free AA activates a variety of proteins involved in the regulation of COX-2 expression, including p38 MAP kinase (Hii et al 1998), peroxisome proliferator-activated receptor γ (Pawliczak et al 2002(Pawliczak et al , 2004 and phosphatidyl inositol-3-kinase (Monick et al 2002). Interestingly, expression of COX-2 was decreased in brains of PLA 2 -deficient mice relative to wild type mice (Bosetti and Weerasinghe, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly cells grown in 6-well dishes were transfected with expression vector or empty vector as described above. After 4 h, medium was changed, and cells were labeled for 16 h with 1 Ci/ml [5,6,8,9,11,12,14 Gene Expression Measurements Using a Real Time Polymerase Chain Reaction-Cells were grown as described above and exposed to EGF, A23187, or MAFP. Total RNA was isolated using an RNeasy kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Upon activation by various stimuli (including but not limited to calcium ionophore (A23187), IL-1␤, tumor necrosis factor-␣, and interferon-␥) cPLA 2 is translocated to the cellular membranes, releasing arachidonic acid from membrane phospholipids (1)(2)(3)(4). Stimuli such as epidermal growth factor (EGF), oxidative stress, or IL-1␤ may also cause cPLA 2 activation through its phosphorylation (5,6). Previously we have reported that cPLA 2 is able to alter gene expression through PPAR-␥ activation and binding to peroxisome proliferator response elements (4).…”
Section: -Kda Cytosolic Phospholipase a 2 (Cpla 2 )mentioning
confidence: 99%
See 1 more Smart Citation